INCIDÊNCIA DE ANOREXIA E DESNUTRIÇÃO ENTRE INDÍGENAS IDOSOS RESIDENTES EM CONTEXTO URBANO, EM CAMPO GRANDE – MS. - VILLALBA, Daniel Lucas Lopes Freitas; ALMEIDA, Isis Marcondes Sodré de; AQUINO, Rayra Jordania Freire; BIANCHI, Melissa Wohnrath; QUADROS, Fatima Alice Aguiar; SACCO, Carolina Maria Startari (ANAIS DO ENIC, 2023)
-